Дослідження на подолі Виповзівського археологічного комплексу - Скороход, В.М.; Капустін, К.М. (Археологія, 2018)
У статті проаналізовано результати археологічних розкопок подолу Виповзівського археологічного комплексу (планіграфія та стратиграфія), здійснено атрибуцію виявлених об’єктів та визначено їх хронологію. В статье проанализированы топография, особенности застройки, стратиграфия подола средневекового Выползова. Здесь в Х в. и, возможно, в ХІІ в. существовала гавань, где осуществлялись ремонт, а также временное хранение разнообразных плавательных средств. Собрано достаточно информации для обоснования гипотезы о существовании портовой зоны в пойменной части памятника. Сделаны также предварительные выводы о начале освоения подола, особенностях его развития на протяжении Х—ХІІ вв., а также функциональном назначении отдельных построек: первые объекты (остатки причалов или пирсов?) появляются в конце ІХ — в начале Х в. В период активного роста Выползова (середина — вторая половина Х в.) тут ремонтировали и временно хранили суда, о чем свидетельствуют находки как минимум шести канав для вытягивания ладей, а также остатки деревянного навеса. После гибели комплекса в конце Х в. возрождение жизни началось не раньше ХІІ в., когда берег реки укрепили деревянными конструкциями и обустроили новую стоянку для судов. В целом, формирование портовой зоны Выползовского археологического комплекса происходило согласно общерусским тенденциям развития городов и поселений раннего этапа становления государства: они возникают в конце IX — начале Х вв. как результат активной военно-политической и торговой деятельности «русов». Фиксация в культурном слое памятника и объектах Х в. не характерных для этого региона керамических форм, украшений, предметов быта свидетельствуют о вероятном перемещении с территории Днепровского Правобережья в Нижнее Подесенье определенных групп переселенцев. Находки арабских дирхемов указывают на систематические торговые контакты с Востоком, и, возможно, исключительный статус поселения — укрепленный торговоремесленный лагерь, используемый для колонизации Днепровского Левобережья. The paper analyzes the topography, peculiarities of development, stratigraphy of the lowland of medieval Vipovziv. The harbour, piers and other specific economic buildings were located in this area during the 10th and probably, in the 12th centuries. According to archaeologicalsurvey of the last years quite enough information was collected to substantiate the hypothesis of the harbor existence in this part of the site. There were made preliminary conclusions about the time of its appearance, functional features of its development during the 10th—12th centuries, aswell asfunctional purpose of the excavated buildings: first objects (remnants of piers (?) on this territory appeared at the end of the 9th - at the beginning of the 10th century: on the time of active growth of settlement agglomeration (in the middle — in the second half of the 10th century) specialized zone of repairs and temporary storage of vessels was carried out, which can be confirmed by the finds of at least six ditches for pulling ships, as well as remnants of a wooden canopy. The complex was ruined at the end of the 10th century, the revival of the latter had begun only in the 12th century. At this time the river bank was strengthened with wooden structures and a harbor was renewed. Basically, port area of the archaeological complex of Vipovziv was formed and developed according to the tendencies of early stage of the state formation of Ancient Rus cities and settlements development: it arose at the end of the 9th — at the beginning of the 10th centuries. as the result of the active political, military and trading activities of the “Rus people”. Finds of non-typical for this region forms of pottery, jewellery and household items indicate the probable movement of certain groups of immigrants from the territory of the right bank of the Dnieper River to the Lower Desna River region; a great collection of Arab dirhams finds indicates the systematic trade contacts with the East, and possibly the exclusive status of the settlement — the fortified trade and craft camp used for colonization of the left bank of the Dnieper River.